Providing Access: Differences in Pediatric Portal Activation Begin at Patient Check-in - Bush, Ruth A.; Vemulakonda, Vijaya M.; Richardson, Andrew C.; Deakyne Davies, Sara J.; Chiang, George J. (Applied Clinical Informatics, 2019)
Background The patient portal interface with individual electronic health records (EHR) was introduced as a tool to enhance participatory medicine. Recent studies suggest adults from racial and ethnic minorities as well as non-English speakers face disproportionate barriers to adoption; however, little data are available for pediatric patients.Objective The purpose of this study was to examine patient portal offers and activation patterns among pediatric urology patients at two geographically diverse tertiary pediatric hospitals.Methods Retrospective analysis of 2011 to 2016 electronic portal audit records was conducted among patients aged 18 and younger with at least one outpatient urology clinic visit at two tertiary academic pediatric hospitals and their affiliated networks. Differences in utilization among parents/caregivers and adolescents were examined using multivariate analysis.Results Of 44,608 individuals seen in a participating urology department during the study period, 21,815 (48.9%) were offered a code for patient portal activation; of these, 8,605 (19.3% of total eligible individuals) activated portal access. Logistic regression demonstrated associations between an offer and site (p < 0.001), being female (p < 0.001), being Asian or white (p < 0.05), being non-Hispanic (p < 0.001), and reporting English as preferred language (p < 0.001). Activating patient portal access was associated with site (p < 0.001), being Asian or white (p < 0.001), and reporting English as preferred language (p < 0.001).Conclusion This study found that demographic variations in portal began with demographic differences in which patients were offered an activation code. Fewer than half of those given an access code activated their account. Preferred language, race/ethnicity, and clinic location were associated with likelihood of portal activation. Although patients are increasingly expected to schedule appointments, manage correspondence, request prescription refills, obtain authorizations and referrals, and communicate with the medical team using the portal, this study suggests that in the pediatric specialty setting many patients and caregivers are not offered the opportunity to access these tools.
Keywords: meaningful use; electronic health records and systems; pediatric health disparities; health information technology; patient portal